2021
DOI: 10.1136/bmjopen-2020-046623
|View full text |Cite
|
Sign up to set email alerts
|

Association between body mass index and short-term mortality in patients with intra-abdominal infections: a retrospective, single-centre cohort study using the Medical Information Mart for Intensive Care database

Abstract: ObjectivesThis study aimed to determine the relationship between the body mass index (BMI) and short-term mortality of patients with intra-abdominal infection (IAI) using the Medical Information Mart for Intensive Care (MIMIC-III) database.DesignRetrospective cohort study.SettingAdult intensive care units (ICUs) at a tertiary hospital in the USA .ParticipantsAdult IAI ICU patients from 2001 to 2012 in the MIMIC-III database.InterventionsIn univariate analysis, we compared the differences in the characteristics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Several prior studies investigated the association between BMI and sepsis-related mortality. However, the conclusion remains inconclusive 18 26–29. In a majority of studies, BMI was shown to be negatively correlated with sepsis-related mortality, and obesity greatly reduced the mortality risk of septic patients 6 18 27–29.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several prior studies investigated the association between BMI and sepsis-related mortality. However, the conclusion remains inconclusive 18 26–29. In a majority of studies, BMI was shown to be negatively correlated with sepsis-related mortality, and obesity greatly reduced the mortality risk of septic patients 6 18 27–29.…”
Section: Discussionmentioning
confidence: 99%
“…However, the conclusion remains inconclusive 18 26–29. In a majority of studies, BMI was shown to be negatively correlated with sepsis-related mortality, and obesity greatly reduced the mortality risk of septic patients 6 18 27–29. Nevertheless, a retrospective observational investigation suggested that obese participants displayed a non-significant increase in mortality risk in adjusted 28-day mortality, relative to non-obese septic controls 26.…”
Section: Discussionmentioning
confidence: 99%